Renewable energy is the basis for achieving sustainable development (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The research deals with the study of renewable energy as the most important available alternatives to traditional energy sources in the world, and a major element and basis for achieving sustainable development. Renewable energy sources are permanent, continuous, renewable and clean, that is, they do not pollute the environment, in addition to the return from their use in the economic and social aspect as a result of their ability to create jobs and provide job opportunities. Therefore, their use has become an urgent necessity and a basic need to achieve sustainable development as a result of its close association with its aspect different. This study dealt with clarifying the concept the renewable energy and its sources, and the concept of sustainable development, its characteristics and dimensions, as well as highlighting the basic role of renewable energy in achieving sustainable development in its various aspect, and reference was made to the experiences of Arab countries and their complex features in the field of renewable energy.